General banking activities and customer services of Janata Bank Limited: UGC corporate branch, Dhaka - Chowdhury, Redwan Ahmed (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.